Organizational culture in Finnish startups and growth companies : a leadership perspective - Mäkiö, Sanna (2019)
Organizational culture is an integral part of every organization and has far-reaching influence on how businesses work. The organizational culture of startups and growth companies has been gaining more and more attention during past years as they seem to pay particular attention to their work cultures and show cultures which highly differ from the cultures of large corporations. However, organizational culture in startups and growth companies have not been widely studied before, mostly due to the newness of the context. This study therefore focused to investigate this topic and takes a leadership approach to examine how the leaders in these new and growing companies approach the issue. The emphasis of the study was on how leaders define organizational culture, why they see it as such an important topic, and can culture in fact be somehow led.